Chapter 9 Poisson Noise Removal in Spherical Multichannel Images: Application to Fermi Data - Schmitt, Jérémy (InTechOpen, 2012)
The Fermi Gamma-ray Space Telescope, which was launched by NASA in June 2008, is a powerful space observatory which studies the high-energy gamma-ray sky Atwood (2009). Fermi's main instrument, the Large Area Telescope (LAT), detects photons in an energy range between 20 MeV to greater than 300 GeV. The LAT is much more sensitive than its predecessor, the EGRET telescope on the Compton Gamma Ray Observatory, and is expected to find several thousand gamma-ray point sources, which is an order of magnitude more than its predecessor EGRET Hartman et al. (1999).